The tragedy of climate change science. (21st October 2022) - Glavovic, Bruce C.; Smith, Timothy F.; White, Iain
ABSTRACT: The science-society contract is broken. The climate is changing. Science demonstrates why this is occurring, that it is getting worse, the implications for human well-being and social-ecological systems, and substantiates action. Governments agree that the science is settled. The tragedy of climate change science is that at the same time as compelling evidence is gathered, fresh warnings issued, and novel methodologies developed, indicators of adverse global change rise year upon year. Meanwhile, global responses to Covid-19 have shown that even emergent scientific knowledge can bolster radical government action. We explore three options for the climate change science community. We find that two options are untenable and one is unpalatable. Given the urgency and criticality of climate change, we argue the time has come for scientists to agree to a moratorium on climate change research as a means to first expose, then renegotiate, the broken science-society contract.